Existence of equilibrium for generalized games in choice form and applications. (1st December 2016) - Patriche, Monica
Abstract : This paper has two central aims: first, to provide simple conditions under which the generalized games in choice form and, consequently, the abstract economies admit equilibrium; second, to study the solvability of several types of systems of vector quasi-equilibrium problems as an application. Our work outlines that there still is much to be gained from using the results concerning the existence of equilibrium of games as tools of research for other optimization problems.